Abstrakčiųjų stimulų žodžių asociacijos - Aleknavičiūtė, Marta Marija (Lietuvių kalba, 2025)
This article presents a word association study aimed at answering two questions: what kinds of associations are elicited by abstract cues and whether participants of different ages produce semantically distinct associations. Participants were presented with 30 abstract cues and asked to type the first word that came to mind after reading each cue. The analysis was based on responses from 389 participants and focused on the semantic content of the associations. The semantic analysis revealed that abstract cues often elicit associations related to concrete objects. For example, emotions are frequently associated with the body, values with other people, and time with movement. The study also found that the semantics of associations is influenced by age: the youngest participants provided more associations with negative connotations than the oldest participants.
Keywords: žodžių asociacijos; žodžių asociacijų testas; abstraktieji konceptai; dalyvių amžius